Effect of different fermentation duration and drying methods on the quality of cocoa bean oil - Toku-Appiah, Bernard (2016)
A thesis submitted to the School of Research and Graduate Studies, Kwame Nkrumah University of Science and Technology, in partial fulfilment of the requirement for the award of the degree Master of Philisophy (M.Phil.) in Postharvest Technology.